Opinion of surveyed nurses on transplantation and reasons for negative public attitudes toward organ donation - Majchrowicz, Bożena; Tomaszewska, Katarzyna; Guzak, Beata (Frontiers in Transplantation, 2023)
Organ transplantation saves thousands of lives every year. Despite growing awareness of transplantation, the issue of obtaining organs for transplantation has been controversial for years. Hundreds of people are waiting in lines all the time for transplantation, for whom it is the only hope for a cure. One extremely important factor contributing to the low number of transplants is the low number of organ donations from deceased donors. Nurses are considered key facilitators of the organ procurement and transplantation process. Their knowledge of and attitudes toward organ donation can influence public opinion, as well as the decisions of their families to donate the organs of the deceased. The purpose of our study was to determine the opinions of surveyed nurses about transplantation and the reasons for negative public attitudes toward organ donation. The survey included 793 nurses employed in surgical wards across Poland with varying levels of job seniority. The survey was conducted between September and October 2022. The research tool was a survey questionnaire. Participation in the survey was anonymous and voluntary. The statistical analysis for independence of variables used the Chi-square test. On the other hand, coefficients based on the Phi and Cramer's V test, as well as Kruskal Wallis non-parametric tests for assessing differences were used to determine the strength of the relationship. During these analyses, in addition to standard statistical significance, the corresponding "p" values were calculated using the Monte Carlo method. According to the nurses surveyed, transplantation is a life-saving procedure. A significant proportion of the nurses (85.6%) believe that there are too few donors in Poland. According to 41.8% of the respondents, this is due to the fear of misdiagnosis of death, for 23.4% it is incompatible with their worldview or religion and 31.8% believe it is due to the belief in the inviolability of the human body after death. The survey showed that the reason for objections to organ transplantation is the deficit in public’s knowledge of cell, tissue and organ donation from both living and dead donors. Therefore it is extremely important to conduct educational campaigns in this regard.